Rescue of noncultivatable human rotavirus by gene reassortment during mixed infection with ts mutants of a cultivatable bovine rotavirus. - Greenberg, H B (1981)
Fastidious human rotaviruses that did not undergo productive infection in tissue culture were rescued by genetic reassortment during mixed infection with a temperature-sensitive (ts) mutant of a cultivatable bovine rotavirus. In this manner, the genes of the fastidious rotavirus that restricted growth in vitro were replaced by the corresponding genes from a tissue culture-adapted rotavirus. We recovered genetically reassorted viruses that grew to high titer and were neutralized specifically by hyperimmune guinea pig type 1 or type 2 human rotavirus antiserum. Preliminary RNA analysis of these clones disclosed that they were indeed viruses with reassorted genes.